(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotation.This article examines the lexical means of expressing temporality in the Russian and Uzbek languages. Temporality, a key linguistic and cognitive category, reflects the temporal characteristics of events and processes within a given cultural and linguistic worldview. Through comparative analysis, the study explores various temporal lexemes—such as adverbs, temporal nouns, idiomatic expressions, and verbal constructions conveying time-related meanings. The research highlights both universal features and culturally specific elements of temporality, illustrating how these are manifested through the lexical resources of each language.